Influence of meteoric smoke particles on the incoherent scatter measured with EISCAT VHF - Gunnarsdottir, Tinna L.; Mann, Ingrid; Feng, Wuhu; Huyghebaert, Devin R.; Haeggstroem, Ingemar; Ogawa, Yasunobu; Saito, Norihito; Nozawa, Satonori; Kawahara, Takuya D. (Annales Geophysicae, 2024)
Meteoric ablation in the Earth's atmosphere produces particles of nanometer size and larger. These particles can become charged and influence the charge balance in the D region (60–90 km) and the incoherent scatter observed with radar from there. Radar studies have shown that, if enough dust particles are charged, they can influence the received radar spectrum below 100 km, provided the electron density is sufficiently high ( >10 9 m 3 ). Here, we study an observation made with the EISCAT VHF radar on 9 January 2014 during strong particle precipitation so that incoherent scatter was observed down to almost 60 km altitude. We found that the measured spectra were too narrow in comparison to the calculated spectra. Adjusting the collision frequency provided a better fit in the frequency range of ± 10–30 Hz. However, this did not lead to the best fit in all cases, especially not for the central part of the spectra in the narrow frequency range of ±10 Hz. By including a negatively charged dust component, we obtained a better fit for spectra observed at altitudes of 75–85 km, indicating that dust influences the incoherent-scatter spectrum at D-region altitudes. The observations at lower altitudes were limited by the small number of free electrons, and observations at higher altitudes were limited by the height resolution of the observations. Inferred dust number densities range from a few particles up to 10 4 cm −3 , and average sizes range from approximately 0.6 to 1 nm. We find an acceptable agreement with the dust profiles calculated with the WACCM-CARMA (Whole Atmosphere Community Climate Model-Community Aerosol Radiation Model for Atmospheres) model. However, these do not include charging, which is also based on models.